The impact of stalking hunt season on long-term stress in big game - Katarzyna Tajchman; Paweł Janiszewski; Patrycja Staniszewska; Vladimir Hanzal; Kornel Kasperek; Aneta Strachecka (BMC Veterinary Research)
Abstract Background The frequent presence of hunters in hunting areas may have a negative impact on wild animals, which may disturb their welfare. Stressors may long affect individual animal species in different ways. Therefore, the study aimed to compare cortisol level in the hair of male mouflons, red deer, and wild boars harvested at the end of the stalking hunting season depending on the age and carcass mass. The cortisol level was determined using the DetectX® Cortisol ELISA Kits. Results The concentration of cortisol in the hair of mouflons was almost six times lower than that of red deer and wild boars. Carcass mass and age researched animals did not affect cortisol levels. Conclusions Stalking hunts most likely do not impact the welfare of big game. There is probably habituation to long-term stress in the animals studied. Mouflons have the ability to respond effectively to specific stressors and are more resistant to long-term stress.